التنوع اللغوي في الجزائر القديمة '' اللغة البونية- دراسة حالة''.: Linguistic variety in ancient Algeria ''The Punic language - case study'' - الطيب, زين العابدين (Maalim, 2021)
linguistic research in the ancient Maghreb in the Punic period requires more research to improve the studies of ancient Algeria. the present study of our article targets this language which is the Punic and which originates from the Phoenician language. Mediterranean peoples in antiquity through the Phoenicians who dominated the North African coast with their trade. which created a common heritage such as religion and culture and the Punic language as the official language of the reign of the king massinisa.which has given as result of this contact from the foundation of Carthage, the birth of the Punic language. and later the neopunic after the fall of Carthage. our study focuses on the diffusion of this language in ancient Algeria, through the different historical and archaeological evidence .